Pengembangan Modul Ajar Kinematika Gerak Lurus Berbasis Pembelajaran Berdiferensiasi pada Kurikulum Merdeka Belajar - Madani, Nofia; Sirait, Judyanto; Oktavianty, Erwina (JPF (Jurnal Pendidikan Fisika) FKIP UM Metro, 2023)
This research is based on changes in the curriculum from the 2013 Curriculum to the Merdeka Curriculum, so that there are adjustments to teaching tools in the form of teaching modules by applying the principle of differentiated learning. Therefore, this study aims to develop a linear motion kinematics teaching module based on differentiation learning for class XI in the Merdeka curriculum. The model used to develop teaching modules is ADDIE (analyze, design, develop, implement, and evaluate) which in this study was carried out only up to the develop stage. In the analyze stage, there is an analysis of the teacher's performance and an analysis of the needs of the students as well as the results of the students' initial assessment. At the design stage, it includes activities for compiling learning objectives and learning objectives flow, selecting suitable learning strategies and creating teaching module storyboards. The results of the storyboard will be executed at the develop stage so that it becomes a complete teaching module. After that, the teaching module is validated by expert validators. Based on the validation results, an average validation percentage of 87.5% was obtained with very decent criteria. Therefore, the teaching modules developed are feasible to be implemented to students